2015
DOI: 10.1038/srep13009
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Combined Treatment with Naringin and Treadmill Exercise on Osteoporosis in Ovariectomized Rats

Abstract: Osteoporosis is a disease characterized by low bone mass and progressive destruction of bone microstructure, resulting in increased the risk of fracture. Previous studies have demonstrated the effect of naringin (NG) or treadmill exercise (EX) on osteoporosis, however, reports about effects of NG plus EX on osteoporosis are limited. This study was designed to investigate the impact of combined treatment with naringin and treadmill exercise on osteoporosis in ovariectomized (OVX) rats. Three months after bilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…The combination of drugs and mechanical stimulation could exert the important regulation of bone remodeling than drugs or mechanical stimulation alone. The combined treatment with naringin and treadmill exercise have an additive effect on reducing the risk of fracture for osteoporosis associated with estrogen deficiency, and low‐magnitude whole‐body vibration combined with alendronate also improved the trabecular architecture in ovariectomized rats . Our previous study has shown that mechanical strain‐induced osteoblast proliferation, differentiation, and mineralization by activating NF‐κB pathway in MC3T3‐E1 cells, moreover, the combination of icariin and mechanical strain stimulation improved osteoinductive potential by up‐regulating the mRNA and protein expressions of ALP, OCN and Col I in osteoblast‐like cells in vitro …”
mentioning
confidence: 97%
“…The combination of drugs and mechanical stimulation could exert the important regulation of bone remodeling than drugs or mechanical stimulation alone. The combined treatment with naringin and treadmill exercise have an additive effect on reducing the risk of fracture for osteoporosis associated with estrogen deficiency, and low‐magnitude whole‐body vibration combined with alendronate also improved the trabecular architecture in ovariectomized rats . Our previous study has shown that mechanical strain‐induced osteoblast proliferation, differentiation, and mineralization by activating NF‐κB pathway in MC3T3‐E1 cells, moreover, the combination of icariin and mechanical strain stimulation improved osteoinductive potential by up‐regulating the mRNA and protein expressions of ALP, OCN and Col I in osteoblast‐like cells in vitro …”
mentioning
confidence: 97%
“…Also, in a recent study by Achiou et al (34), daily aerobic exercise plus the use of sclerostine antibody for 9 weeks increased the markers of bone formation, such as osteocalcin, and prevented destructive effects of glucocorticoids on bone mineral density, including bone mineral capacity, bone density, and the volume of bone mass connective tissue in male Wistar rats injected with glucocorticosteroids. Sun et al (35), also revealed that regular aerobic exercises combined with Naringin for 60 days led to an increase in the osteocalcin expression and a reduction in CTX-1 type I in male Wistar rats. Researchers believe that the effects of exercise training on the bone are particularly dependent on the intensity and duration of the exercise; the intensity or load on the bone is more important than the exercise time (36).…”
Section: Discussionmentioning
confidence: 93%
“…In this study, the level of the bone resorption factor, CTX, was significantly decreased by IR training, which resulted in enhanced bone formation. Previous study reports that a high level of CTX is associated with lower BMD values in osteoporosis (Sun et al., ).…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported that osteoblasts and osteoclasts perceive and respond to mechanical stimulation, and are regulated by the activation of alkaline phosphatase (ALP), runt-related transcription factor 2 (Runx2), sirtuins (SIRTs) and bone morphogenic proteins (BMPs) (Chen et al, 2008;Kanno, Takahashi, Tsujisawa, Ariyoshi, & Nishihara, 2007;Kim et al, 2016;Zhang et al, 2017). In addition, several studies have also shown that mechanical stimulation may inhibit the differentiation of osteoclasts and the activation of bone resorption (Sun et al, 2015;Suzuki, Yoshimura, Deyama, Suzuki, & Kitagawa, 2008). The effect of exercise training is related to the mechanical stimulation on bone caused by contraction of muscle (Oh, Tanaka, Naka, & Igawa, 2016).…”
Section: Introductionmentioning
confidence: 99%